Ujaran lisan oleh wanita Kelantan dalam perniagaan tekstil di Pasar Besar Siti Khadijah - Abd. Nasir, Siti Noridayu; Abdul Halim, Hazlina (University of Melaka, 2022)
The presence of women in helping to improve the economic status of the family is a phenomenon. In fact, the skills possessed by women in Malaysia are seen as comparable to those of men. Nowadays, women play a big role in various fields involving business. This is because, business activities can provide a good income to women nowadays. Therefore, this study aims to look at the interaction of the expressions of women traders used in the Siti Khadijah Central Market, Kelantan. Then, identify dialects with the aim of attracting customers to buy their sales products. Next, discuss the types of textile products that are the choice of goods sold at Pasar Besar Siti Khadijah. This study applies Brown & Yule 1983 Discourse Analysis Theory used in the customer persuasion process. The results of the study show that the use of dialects is used to attract buyers because of the competition of stores that sell the same textile products. In fact, the dialect is used entirely by women traders to preserve the Kelantan dialect which is their daily language of communication. Furthermore, textile products sold at Pasar Besar Siti Khadijah are textiles for women's needs. Therefore, presumptions are used for the purpose of persuading the customer and asserting that the price given is best for the customer.